Targeting the NRF-2/RHOA/ROCK signaling pathway with a novel aziridonin, YD0514, to suppress breast cancer progression and lung metastasis. (28th June 2018) - Li, Dengfeng; Wang, Hong; Ding, Ye; Zhang, Ziwei; Zheng, Zhi; Dong, Jiabin; Kim, Hyejin; Meng, Xiaojing; Zhou, Qianjun; Zhou, Jia; Fang, Lin; Shen, Qiang
Abstract: Metastasis is a major cause of breast cancer-associated mortality. Natural products extracted from herbs provide rich bioactive compounds with anticancer efficacy but may have limited or moderate potency and considerable toxicity. We developed a novel aziridonin, YD0514, by aziridinating oridonin, a natural product of the medicinal herb Rabdosia rubescens. In this study, we found that YD0514 significantly inhibited proliferation, motility, and adhesion of metastatic breast cancer cell lines MDA-MB-231, GI101, GILM2, and GILM3. YD0514 also decreased the protein expression of matrix metalloproteinases 2 and 9 (MMP2 and MMP9), focal adhesion kinase (FAK), and integrin family members. Importantly, YD0514 suppressed the growth of metastatic breast cancer xenograft tumors and significantly inhibited lung metastasis in vivo . Lastly, we showed that YD0514's anti-metastatic effect on highly aggressive breast cancer is mediated via regulating the NRF-2/RHOA/ROCK signaling pathway. These results demonstrate that YD0514, the first active analog based on an oridonin D-ring modification, has the potential to be developed as an anti-metastasis therapy for patients with metastatic cancers. Highlights: YD0514 is a novel aziridonin that significantly inhibits the motility of metastatic breast cancer cells. YD0514 suppresses xenograft tumor growth and lung metastasis from highly metastatic, triple-negative breast cancer cells YD0514 suppresses the expression of MMPs and integrins in metastatic breast cancer cells. YD0514 inhibits metastatic breast cancer growth and progression partially via the NRF2/RHOA/ROCK pathway.